Guest

if tan beta = (tan alpha + tan gama)/(1+ tan alpha . tan gama), prove that sin2beta=(sin2alpha + sin2gama)/(1+sin2alpha . sin2gama)

if tan beta = (tan alpha + tan gama)/(1+ tan alpha . tan gama), 
prove that sin2beta=(sin2alpha + sin2gama)/(1+sin2alpha . sin2gama)

Grade:11

2 Answers

grenade
2061 Points
7 years ago
from the above statement it is clear that 
beta=alpha+gama
grenade
2061 Points
7 years ago
oops mistook

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free